Creative Economy Shocks and Tourism Dynamics: A DSGE Approach - Savitri, Savitri (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This article introduces the use of Dynamic Stochastic General Equilibrium (DSGE) as a sophisticated macroeconomic approach to analyze the impact of shocks on the relationship between tourism and the creative economy. Background Problems: Tourism and the creative economy are two interrelated sectors that have a strategic role in supporting sustainable development. The relationship between the two is often difficult to explain with conventional approaches such as panel regression and Structural Equation Modeling (SEM), because these methods tend to be static and are less able to capture the dynamics of global shocks. Research Methods: The DSGE model was built using secondary data from UNWTO, the World Bank, and the IMF, and includes four main agencies: households, governments, the tourism sector, and the creative sector. Finding/Results: The estimated results show that the digitalization shock has a significant positive impact by increasing creative output, tourism consumption, and creative GDP contribution in the short and long term. In contrast, the pandemic shock caused a major contraction in tourist arrivals and tourism output, although a gradual recovery occurred over several periods. Conclusion: The findings of this study have practical implications for policymakers, particularly in designing creativity-based recovery strategies, strengthening creative ecosystems, and encouraging sustainable tourism growth in the digital and post-pandemic era.